Adherence to Mediterranean diet of children living in small Southern Italian villages. (18th May 2020) - Grassi, Tiziana; Bagordo, Francesco; Panico, Alessandra; De Giorgi, Mattia; Idolo, Adele; Serio, Francesca; Tumolo, Maria Rosaria; De Donno, Antonella
Abstract: A cross-sectional study was conducted in the primary schools of five small villages of Salento Peninsula to evaluate the adherence to the Mediterranean Diet (MD) of 282 6-8-years old children in relation to lifestyles and socio-economic factors. The parents of children completed a self-administered questionnaire to evaluate the prevalence of personal, behavioural and socio-economic factors of their sons. Children's anthropometric measurements were also taken. The adherence to the MD was assessed using the Mediterranean Diet Quality Index for Children and Adolescents (KIDMED). The chi-square test was used to detect any differences among groups of children. Overall, 27.0% of children showed low adherence to the MD (KIDMED ≤3), 59.6% medium adherence (KIDMED 4–7) and 13.5% high adherence (KIDMED ≥8). The adherence to the MD was associated with the educational level (whether graduated or not) of the mother and the occupational status (whether employed or not) of both parents.